Robot-Assisted vs. Open Appendicovesicostomy in Pediatric Urology: A Systematic Review and Single-Center Case Series - Juul, Nikolai; Persad, Emma; Willacy, Oliver; Thorup, Jorgen; Fossum, Magdalena; Reinhardt, Susanne (Frontiers in Pediatrics, 2022)
Introduction: Appendicovesicostomy (APV) is the preferred choice for long-term urinary diversion in pediatric urology. The introduction of robot-assisted laparoscopic techniques has been correlated to superior cosmesis and convalescence and is now increasingly implemented for APV procedures. We aimed to perform a systematic review of the literature comparing open versus robotic APV regarding possible differences in postoperative outcomes and to evaluate these findings with our own initial experiences with robotic APV compared to our previous open procedures. Methods: We evaluated the first five patients undergoing robotic APV at our institution and compared one-year outcomes with a consecutive series of 12 patients undergoing open APV. In a systematic literature review, we screened studies from PubMed, EMBASE and CENTRAL comparing open and robotic APV in pediatric urology (current to December 2021) and performed meta-analyses on postoperative outcomes comparing the two groups and evaluated the grade of evidence. Results: We found significantly shortened postoperative length of stay in the robotic group (p=0.001) and comparable one-year complication rates in robotic versus open APV patients. We systematically screened 3204 studies and ultimately included three non-randomized studies comparing postoperative outcomes of robotic and open APV for quantitative analysis. The open and robotic approaches performed equally well regarding overall postoperative complications, surgical reintervention, and stomal stenosis. Two of the included studies reported comparable stomal continence rates and shortened postoperative length of stay in the robotic group, in agreement with the findings in our own series. Conclusion: Robotic APV is equally safe to the conventional open approach with additional advantages in postoperative hospitalization length.